How to think : building your mental muscle - Reid, Stephen. (Prentice Hall, 2002)
"This is the book that explains how to think, presenting a range of thinking tools and techniques to improve the quality and range of thinking, using everyday examples in work and life to highlight key points. How to Think is the mind-gym to work out every mental muscle and give you real mind power. And, improving the quality of your thinking will improve the quality of your life - at work and at home."--BOOK JACKET.